Integration Strategic Plan Coorporate Social Responsibility in the Regional Development Planning of Buleleng Regency - Made Anik Wiryantini; Putu Indah Rahmawati; Ni Made Ary Widiastini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study is aimed at understanding the CSR (Corporate Social Responsibility) program which is still applying in Buleleng regency, in order to explore the company’s perception regarding the plan of CSR (Corporate Social Responsibility) integration with regional development plan in Buleleng regency and arranging a CSR (Corporate Social Responsibility). This study uses a qualitative method with study subjects including company and the corporate social and environmental responsibility Facilitation team of Buleleng regency. The study’s results show that (1) CSR (Corporate Social Responsibility) program which has been applying so far in Buleleng regency has encountered several obstacles such as the data form and activity administration. (2) The company perception of integration plan shows that the company supports the plan in general as long as it continues to adopt the company’s business interests. (3) The form of integration expected by the company can be carried out at the planning and implementation stages of activity. (4) The priority areas that planned to receive CSR (Corporate Social Responsibility) founding, they are must be the areas which is in line with goals and objectives of the Buleleng regency local government plan. (5) The Strategic Plan for Integration of CSR (Corporate Social Responsibility) with regional development plan is described in the strategy for implementing activities and in the form of activity proposals.